The Hyperactivity–Impulsivity–Irritiability–Disinhibition–Aggression–Agitation Domain in Alzheimer’s Disease: Current Management and Future Directions - Keszycki, Rachel M.; Fisher, Daniel W.; Dong, Hongxin (Frontiers in Pharmacology, 2019)
Behavioral and psychological symptoms of dementia (BPSD) afflict the vast majority of patients with dementia, especially those with Alzheimer’s Disease (AD). In clinical settings, patients with BPSD most often do not present with just one symptom. Rather, clusters of symptoms commonly co-occur and can thus be grouped into behavioral domains that may ultimately be the result of disruptions in overarching neural circuits. One major BPSD domain routinely identified across patients with AD is the Hyperactivity-Impulsivity-Irritiability-Disinhibition-Aggression-Agitation (HIDA) Domain. The HIDA Domain represents one of the most difficult set of symptoms to manage in AD and accounts for much of the burden for caregivers and hospital staff. Although many studies recommend non-pharmacological treatments for HIDA Domain symptoms as first-line, they demonstrate little consensus as to what these treatments should be and are often difficult to implement clinically. Certain symptoms within the HIDA Domain also do not respond adequately to these treatments, putting patients at risk and necessitating adjunct pharmacological intervention. In this review, we summarize the current literature regarding non-pharmacological and pharmacological interventions for the HIDA Domain and provide suggestions for improving treatment. As epigenetic changes due to aging and AD both cause dysfunction in drug-targeted receptors, we propose that HIDA Domain treatments could be enhanced by adjunct strategies that modify these epigenetic alterations and thus increase efficacy and reduce side effects. To improve the implementation of non-pharmacological approaches in clinical settings, we suggest that issues regarding inadequate resources and guidance for implementation should be addressed. Finally, we propose that increased monitoring of symptom and treatment progression via novel sensor technology and the “DICE” (Describe, Investigate, Create, and Evaluate) approach may enhance both pharmacological and non-pharmacological interventions for the HIDA Domain.